Online debates on the regulation of child pornography and copyright: two subjects, one argument? - Simon Berghofer; Saskia Sell (Internet Policy Review, 2015)
Our study analyses the online discourse related to the failure of two internet policy initiatives in two democratic countries: the German Access Impediment Act (AIA) and the US-American Stop Online-Piracy Act (SOPA). Even though the two policy proposals have different goals, they were both heavily opposed in public and led to online and offline protests. We examined the discourse surrounding the policy debates through a qualitative content analysis of 742 online articles on general and special interest platforms in order to reconstruct the main actor coalitions and narrative patterns. Comparing two national discourses, we find that opponents of the legislation initiatives employ similar arguments. Protests framed the legislation attempts as being incompatible with an internet-specific interpretation of fundamental norms and ideas about freedom of expression. Consequently we argue that the internet can provide a communication forum in which netizen seem to base their positions on a set of transnational beliefs and ideas about internet regulation.
Keywords: 300; Child pornography; Copyright; Internet blockings; Content filtering